Infectious keratoconjunctivitis in semi-domesticated Eurasian tundra reindeer (Rangifer tarandus tarandus): Microbiological study of clinically affected and unaffected animals with special reference to cervid herpesvirus 2 - Sanchez Romano, Javier; Mørk, Torill; Laaksonen, Sauli; Ågren, Erik; Nymo, Ingebjørg Helena; Sunde, Marianne; Tryland, Morten (BMC Veterinary Research, 2018)
Source at https://doi.org/10.1186/s12917-018-1338-y . Background Infectious keratoconjunctivitis (IKC) is one of the most common ocular diseases in ruminants worldwide. In addition to keratitis and conjunctivitis, animals with IKC can develop uveitis, corneal ulcer, and in severe cases, blindness. The bacteria Moraxella spp. has been described as the primary causative agent of infectious bovine keratoconjunctivitis (IBK) in cattle (Bos taurus), while Chlamydia spp. and Mycoplasma conjunctivae are considered the main causative agents of IKC in sheep (Ovis aries). Previous studies indicated cervid herpesvirus 2 (CvHV2) as the primary causative agent of IKC in semi-domesticated reindeer (Rangifer tarandus tarandus). The aim of the study was to investigate the presence and prevalence of potential pathogens for IKC in reindeer, and compare the ocular microbiota of animals with IKC, with apparently healthy animals. Results Semi-domesticated reindeer (n = 341), with (n = 108) or without (n = 113) ocular clinical signs, or with no information on clinical status (n = 120), were sampled in Norway, Sweden and Finland in 2010–2014. Seroprevalence was 37.4% for alphaherpesvirus (95/254), 3.8% for gammaherpesvirus (8/211) and 7.1% for pestivirus (15/211) (ELISA). PCR analyses of conjunctival swab samples revealed a prevalence of 28.5% for CvHV2 (57/200), 11.9% for Chlamydiaceae (16/135) and 1.0% for M. conjunctivae (2/197). Bacteriological cultivation of 202 conjunctival swab samples revealed bacterial growth from 75.2% of the samples, with Moraxella spp. being isolated from 21.6% (11/51) of the animals with and 5.6% (5/84) without ocular clinical signs. A significant association (p < 0.001) existed between the presence of clinical signs of IKC and CvHV2 DNA in the affected eyes, an association that was not present for other microorganisms. Conclusions These results support the hypothesis that CvHV2 is the primary agent of IKC in semi-domesticated reindeer in Fennoscandia, with Moraxella bovoculi being a secondary ...